Analisis Kinerja AES dan RC6 pada File Multimedia - Sugiyatno Sugiyatno; Hafidz Maulana Rahman (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2026)
This study aims to analyze and compare the performance of symmetric cryptographic algorithms, namely Advanced Encryption Standard (AES) and Rivest Cipher 6 (RC6), in securing multimedia files. The research employs a quantitative experimental approach using various file formats, including JPG, PNG, MP3, and MP4, with different file sizes. Performance evaluation is conducted based on three main parameters: encryption time, decryption time, and throughput. The implementation is carried out in a controlled local environment using Python to ensure consistency and accuracy of measurements. The results show that AES consistently outperforms RC6 in terms of faster encryption and decryption processes as well as higher and more stable throughput across all tested formats and file sizes. In contrast, RC6 exhibits higher computational overhead due to its complex arithmetic operations, resulting in slower processing time and less stable performance. Furthermore, the findings indicate that file size and format significantly influence algorithm performance, where larger and more complex multimedia data require higher processing time. This study contributes a comprehensive multi-format evaluation framework that provides practical insights for selecting efficient cryptographic algorithms in real-world multimedia security applications.